VO-2 assisted unit cell for designing THz reconfigurable Reflectarray antenna - Qureshi, Suhail Asghar; Kamarudin, Muhammad Ramlee; Abbasi, Muhammad Inam; Abidin, Zuhairiah Zainal; Dahri, Muhammad Hashim (2023)
A hybrid half-wavelength model of gold and Vanadium Oxide (VO-2) is presented in this paper operating at 1.1 THz. With the temperature variation, VO-2 changes its state from insulator to metallic which causes the phase response of the unit cell to change. The phase shift of 198 is obtained based on the switching mechanism of VO-2. This provides a hint at the capacity of VO-2 being used as the switching mechanism at the terahertz band for designing the reconfigurable reflectarray antenna.